Pemanfaatan Media Audio Visual Dalam Meningkatkan Motivasi Belajar Siswa Kelas X SMA Negeri 5 Maros Pada Mata Pelajaran Bahasa Indonesia - Nurul Nurul; Suardi Suardi; Fadilah Herawati (STIKes Ibnu Sina Ajibarang, 2024)
This research is classroom action research which aims to determine the improvement in student learning outcomes in the Indonesian language subject for class X SMA Negeri 5 Maros. The subjects of this research were class X of SMA Negeri 5 Maros for the 2023/2024 academic year with a total of 36 people. This research was carried out in two cycles and each cycle consisted of 6 meetings. The results of this research show that the application of audio-visual based learning media can improve the effectiveness and learning outcomes of students in Indonesian language subjects. Quantitative analysis shows that learning outcomes in the initial test were 38.88%, in cycle I there was an increase of 52.77% and then in cycle II it was 100%. This means that there is a significant increase in student learning outcomes.